How to build an extensional basin in a contractional setting? Numerical and physical modelling applied to the Mejerda Basin at the front of the eastern Tell of Tunisia. (December 2019) - Khelil, Mannoubi; Souloumiac, Pauline; Maillot, Bertrand; Khomsi, Sami; Frizon de Lamotte, Dominique
Abstract: In Tunisia, Africa-Eurasia convergence resulted in the Tell fold-and-thrust belt (FTB), part of the Tell-Rif (or Maghrebides), associated, to the south, to the Atlas intra-continental belt. The Mejerda rift-basin is developed over the compressional boundary between the Tell and the Atlas. The main objective of this study is to identify the mechanism responsible for such a basin development. The abundance of Triassic salt structures in the northern Atlas, compared to the Tell, suggests a friction change along the basal décollement formed by the salt level. This frictional contrast is expected to produce a heterogeneous deformational response and complex structures. On this basis, numerical and analogue modelling were used to investigate the impact of a friction change on the deformation style. The kinematic approach of the limit analysis theory was applied here, via the software Optum G2. The onset of faulting in all numerical tests reveals extensional faults appear at the friction boundary. Beyond the onset of faulting, sandbox experiments show extensional features such as collapsing blocks and extensional faults. Overall, the adopted numerical and physical approaches showed evidences of extension. In particular, the experiment using sandpaper and Silicon putty (PDMS) for the décollement transition shows viscous deformation, mimicking diapiric movement. These observations of numerical and physical model behaviors highlight that compression can produce an extensional basin at the top of a thrust wedge, as expression of a strong basal friction change. Hence, the Mejerda basin is interpreted as a wedge-top basin. It developed, during the growth of the Tell and Atlas FTBs. The same configuration likely exists in other mountain belts: the case of the Molasse Basin between the Jura and the Western Alps is advocated. Highlights: Abrupt basal friction decrease induces extension, during contractional settings. Graben generates, in sandbox, remobilizing silicon and mimicking "salt diapir loading". Transition toward a richer salt province may develop extensional wedge-top basin, in compression. Mejerda extensional wedge-top basin set up occurred during Africa-Eurasia collision.